José Aloísio de Campos : trajetória e representações sobre o seu reitorado na Universidade Federal de Sergipe - Santos, Patrícia Francisca de Matos (2015)
This dissertation explores the experience of an intellectual of education, professor Jose Aloisio de Campos (1914-1986). In It is investigated the trajectory of this character, who served as The headmaster of the Federal University of Sergipe (UFS), between 1976-1980, in addition to the representations that the society of Sergipe built on their administrative actions by the Institution. The work employs as main sources the oral testimony, file documentation sponsered by Campo´s family and also by UFS. To examine them, we made use of the techniques provided by |oral history| and the |critical documentary|. The interpretation of the records was mediated by Jean-François Sirinelli´s concepts of intellectuallity, Pierre Bourdieu´s trajectory and Roger Chartier´s representation. The Final Results of this study allow the observation that Jose Aloisio de Campos had important and decisive role as intellectual and public man in the various fields in which he acted in public means of municipal, state and federal. As The headmaster of the Federal University of Sergipe promoted relevant administrative reforms and academic which have enabled this institution thriving on the educational scene as a reference for quality in education. In addition, his administration has been understood as a moment in history that also collaborated to organize the political and economic structure of UFS and that it is remembered until today in the memory and in the actions of some characters. The research, thus contributes to the expansion of a local experience little visited by the history of education in the state of Sergipe, despite the consistent performance of the historians of education in Sergipe, over the last 15 years, inside and outside of the mentioned institution.